Стратегія формування конкурентних переваг підприємств молочної галузі в умовах інтенсивної конкурентної боротьби - Крайнюченко (Форноляк), Ольга Феодосіївна; Гарастовська, Альона Вікторівна (My University, 2022)
Визначено особливості формування конкурентних переваг задля забезпечення стійкої конкурентної позиції підприємства на молочному ринку. Окреслено основні етапи формування ефективних конкурентних переваг на підприємствах молочної галузі.

The peculiarities of the formation of competitive advantages in order to ensure a stable competitive position of the enterprise in the dairy market are determined. The main stages of the formation of effective competitive advantages at enterprises of the dairy industry are outlined.
Keywords: кафедра маркетингу; конкурентні переваги; стратегія; молочна галузь; конкурентна боротьба; competitive advantages; strategy; dairy industry; competitive struggle